Karakteristik Lansia dengan Kemandirian Aktifitas Sehari-hari - I Wayan Suardana (Jurnal Gema Keperawatan, 2013)
Purpose of this research is to know correlation between characteristic and life independence in performing daily activities in elderly. This research is a descriptive study with cross-sectional correlation approach with total sampling(60 patients). Data was collected using interviews and observation. To Analysis relationship between the variable characteristics of the respondents with self-reliance made by Spearman rank correlation test and chi square. The results of this study  showed the majority of respondents in this study had a relatively independent level of independence as many as 41 people (68%) and partly classified as mild independenceas many as 19 people (32%). Based on the characteristics of the respondents there was a relationship between the age of independence (p = 0.000, r = -0.517), gender was not associated with independence (p = 0.077, X2 = 0.781) Education has ties to the independence of the elderly (p = 0.001, r = - 0.425). Economic status was not related to the independence of the elderly (p = 0.723, r = -0.047). Marital status related to the independence of the elderly (p = 0.013, X2 = 8.652). The health status of the elderly is not associated with independence (p = 0.08, r = 0.228). It is expected the elderly to maintain  independence with frequent activities. Always check their health regularly and follow gymnastics elderly.